2019
DOI: 10.1021/acssuschemeng.8b05059
|View full text |Cite
|
Sign up to set email alerts
|

All-Wood Composite Material by Partial Fiber Surface Dissolution with an Ionic Liquid

Abstract: Synthetic structural materials of high mechanical performance are typically either of large weight (for example, steels, and alloys) or involve complex manufacturing processes and thus have high cost or cause adverse environmental impact (for example, polymer-based and biomimetic composites). In this perspective, low-cost, abundant and nature-based materials, such as wood, represent particular interest provided they fulfill the requirements for advanced engineering structures and applications, especially when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…The recycling of discarded NFs such as wood flour (WF), rice chaff (RF), bagasse fiber (BF), and sisal fiber (SF) has caught more and more people’s attention with the upgrading of environment protection as a priority. Compared with inorganic fibers such as glass fiber and carbon fiber, NF has advantages in terms of light weight, low cost, high strength, high modulus, and biodegradation, and have been widely used to prepare green composites [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The recycling of discarded NFs such as wood flour (WF), rice chaff (RF), bagasse fiber (BF), and sisal fiber (SF) has caught more and more people’s attention with the upgrading of environment protection as a priority. Compared with inorganic fibers such as glass fiber and carbon fiber, NF has advantages in terms of light weight, low cost, high strength, high modulus, and biodegradation, and have been widely used to prepare green composites [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose is considered an abundant renewable resource of great potential for bio-based materials and products. The attractive mechanical properties of this biopolymer enable production of a wide range of cellulose-based materials (Zhang et al 2017;Khakalo et al 2019). The presence of many hydroxyl groups, which gives cellulose its remarkably high hydrophilicity, and the extensive network of inter-and intramolecular hydrogen bonds, which provides relatively high chemical and thermal stability, make cellulose an attractive material for filtration membranes (Woodings 2001;Ś lusarczyk and Fryczkowska 2019).…”
Section: Introductionmentioning
confidence: 99%
“…conventional viscose and carbamate processes and solvent systems for cellulose such as DMF/N 2 O 4 or DMSO/N 2 O 4 , CF 3 COOH, HCOOH/H 2 SO 4 and Cl 2 CHCOOH) and non-derivatizing solvents, which do not alter the cellulose chemistry but break hydrogen bonds within the cellulose microfibrils during the dissolution process (e.g. cupro, NMMOÁH 2 O and lithium chloride/N,Ndimethylacetamide (LiCl/DMAc)) (Pinkert et al 2009;Khakalo et al 2019). Existing conventional cellulose dissolution and membrane fabrication (both derivatizing and non-derivatizing solvent-based processes) require expensive, hazardous chemicals and cause significant pollution, so there is a need for novel non-derivatizing solvents whose dissolution mechanism maintains the beneficial characteristics of cellulose as a membrane material (Zhang et al 2017;Khakalo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wood is a traditional biomaterial with cellular structure [1] and has been long time widely studied and used for building and furniture construction. Very recently, some reports showed that the common wood can be treated as a high-strength material [2] or developed as wood-based functional materials [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%